A influência de informações socioambientais e de governança na decisão do investidor - Leite, Ígor Figueirêdo (2020)
The present study aimed to verify the impact of the presentation of socio-environmental and governance information in the investment decision making. In order to fulfill the general objective, a survey was carried out with 409 respondents who were submitted to the questionnaires between October 31 and November 10 of 2019, to analyze the research data, we used the parametric test of correspondence analysis and t-student and the nonparametric tests Chi Square and Kruskal-Walis test, we also used the Tobit Regression. Being its dissemination carried out through social networks, it should be noted that two questionnaires were prepared, in which one of them presented socio-environmental and governance information and the other did not, this difference arises to buy the results between the two questionnaires. Among the results of the research, the factors identified with the highest frequency of importance for the investment analysis process were, respectively, Profitability, Governance Issues and Profitability. It was also identified that the presentation of socio-environmental and governance information does not interfere in the decision-making of the Brazilian investor, among the reasons for this result is that the Brazilian investor is not yet concerned with socio-environmental and governance factors, being more concerned with the return obtained. In addition, it was evidenced that the investor's decision is negatively influenced by the investor's perception of risk, in the sense that the less risky the investor understands that that asset is, the greater the investment made. At the same time, it was identified that there is a difference in the investment decision according to the investor profile. The investment decision is negatively impacted by the perception of risk and the aggressive investor will be less influenced by social and environmental information. Thus, the study contributes to the national literature since it sought to identify whether socio-environmental and governance information has any impact on decision making, as well as seeking to identify whether different profiles have different decision making. The relevance of the study can be evidenced since it sought to address a little explored subject in Brazil, which is the impact of the presentation of socio-environmental and governance information, as well as seeking to understand the behavior of members of investment groups.